Morphological, electrophysiological, and molecular alterations in foetal noncompacted cardiomyopathy induced by disruption of ROCK signalling - Sedmera, David; Olejnickova, Veronika; Sankova, Barbora; Kolesova, Hana; Bartos, Martin; Kvasilova, Alena; Phillips, Lauren C.; Bamforth, Simon D.; Phillips, Helen M. (Frontiers in Cell and Developmental Biology, 2024)
Left ventricular noncompaction cardiomyopathy is associated with heart failure, arrhythmia, and sudden cardiac death. The developmental mechanism underpinning noncompaction in the adult heart is still not fully understood, with lack of trabeculae compaction, hypertrabeculation, and loss of proliferation cited as possible causes. To study this, we utilised a mouse model of aberrant Rho kinase (ROCK) signalling in cardiomyocytes, which led to a noncompaction phenotype during embryogenesis, and monitored how this progressed after birth and into adulthood. The cause of the early noncompaction at E15.5 was attributed to a decrease in proliferation in the developing ventricular wall. By E18.5, the phenotype became patchy, with regions of noncompaction interspersed with thick compacted areas of ventricular wall. To study how this altered myoarchitecture of the heart influenced impulse propagation in the developing and adult heart, we used histology with immunohistochemistry for gap junction protein expression, optical mapping, and electrocardiography. At the prenatal stages, a clear reduction in left ventricular wall thickness, accompanied by abnormal conduction of the ectopically paced beat in that area, was observed in mutant hearts. This correlated with increased expression of connexin-40 and connexin-43 in noncompacted trabeculae. In postnatal stages, left ventricular noncompaction was resolved, but the right ventricular wall remained structurally abnormal through to adulthood with cardiomyocyte hypertrophy and retention of myocardial crypts. Thus, this is a novel model of self-correcting embryonic hypertrabeculation cardiomyopathy, but it highlights that remodelling potential differs between the left and right ventricles. We conclude that disruption of ROCK signalling induces both morphological and electrophysiological changes that evolve over time, highlighting the link between myocyte proliferation and noncompaction phenotypes and electrophysiological differentiation.